The Christian Tradition. - Keen, Ralph (Lanham : Rowman & Littlefield Pub. Group, 2008)
The Christian Tradition introduces students at the beginning of a new millennium to a religion that has evolved over and shaped two previous millennia. With particular focus placed on the social and cultural background to this tradition, the text provi.
Chapter 07. The Monastic Microcosm: The Benedictine Norm and ReformChapter 08. The Expansion of the Church: First Missionary Movements and the Crusades; Part III. Medieval Western Christian Culture; Chapter 09. Carolingian Culture and Religion: A Medieval Renaissance; Chapter 10. Scholasticism: From Anselm to Aquinas; Chapter 11. The Church and the Law: The Investiture Controversy; Chapter 12. The Mendicant Orders and Lay Movements: New Forms of Religious Life; Chapter 13.
Includes bibliographical references (p. 387-390) and index.
Description based on print version record.
Keywords: Church history; Christianity; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Electronic books